2020
DOI: 10.3390/met10081029
|View full text |Cite
|
Sign up to set email alerts
|

Leaching Behavior of Gold and Silver from Concentrated Sulfide Ore Using Ammonium Thiosulfate

Abstract: Ammonium thiosulfate is an alternative lixiviant for the hydrometallurgical treatment of sulfide gold ores. The present study is primarily focused on ammonium thiosulfate leaching of gold (Au) and silver (Ag) from the sulfide ore (Sunshin mine in Korea). The main chemical composition of the concentrate was Au (84 ppm), Ag (852 ppm), Fe (18.9%), Si (23.2%), and S (21.1%). The effects of various parameters on the process, such as leaching time (1–4 h), ammonium thiosulfate concentration (0.05–0.5 M), copper sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…It is important to note that the experiments on the Akeshi and Hishikari ores were run for only 5 h, and the study did not provide detailed mineralogy or an indication of whether or not some gangue minerals in the ore could have been consumers of the reagent. In this current study, the experiments were run for 24 h; however, the extractions achieved with the three ores after 5 h were already close to those achieved after 24 h. These findings are further supported by a study conducted by Bae et al [39] that also investigated the effect of (NH 4 ) 2 S 2 O 3 , NH 3 , and Cu(II) concentrations on the leaching of gold ores. This ore had a much higher Au and Cu content (84 g/t and 0.38 wt.%, respectively) compared to the three ores under study.…”
Section: Effect Of (Nh4)2s2o3 Concentrationsupporting
confidence: 86%
See 1 more Smart Citation
“…It is important to note that the experiments on the Akeshi and Hishikari ores were run for only 5 h, and the study did not provide detailed mineralogy or an indication of whether or not some gangue minerals in the ore could have been consumers of the reagent. In this current study, the experiments were run for 24 h; however, the extractions achieved with the three ores after 5 h were already close to those achieved after 24 h. These findings are further supported by a study conducted by Bae et al [39] that also investigated the effect of (NH 4 ) 2 S 2 O 3 , NH 3 , and Cu(II) concentrations on the leaching of gold ores. This ore had a much higher Au and Cu content (84 g/t and 0.38 wt.%, respectively) compared to the three ores under study.…”
Section: Effect Of (Nh4)2s2o3 Concentrationsupporting
confidence: 86%
“…It was found that increasing the (NH 4 ) 2 S 2 O 3 concentration from 0.05 M to 0.5 M increased gold extraction, reaching an impressive 99% extraction at 0.5 M. This extraction was however much faster than what this study achieved. This must be attributed to the fact that the experiment conducted by Bae et al [39] was conducted at a much finer grind size (45.3 µm) and a much lower solids loading (20%), which significantly improved leaching.…”
Section: Effect Of (Nh4)2s2o3 Concentrationmentioning
confidence: 99%
“…The high reducing activity of thiosulfates is used in a number of applications, among them: textile industry (removal of an excess bleach) [1], leather industry (treatment of hides) [2], water conditioning systems (dechlorination of a ballast water) [3], analytical chemistry [4]. As a complexing reagent, sodium and ammonium thiosulfates are considered as a possible replacement for highly toxic cyanides in the extraction of precious metals (gold, silver) from ores [5]:…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the authors propose the use of thiosulfate as leaching reagent to recover the copper contained in PCBs, as an hydrometallurgical alternative to leaching in an alkaline medium, due to its complexation capacity [ 43 , 44 , 45 , 46 ] and degree of stability in the compound formed, which is the copper thiosulfate [ 47 ]. Generally the formation of this compound is reported as a problem in the leaching of precious metals (Au and Ag) due to the consumption and degradation of thiosulfate that occurs, but in this case the authors have taken the advantage of this tendency to recover the copper present in these types of wastes.…”
Section: Introductionmentioning
confidence: 99%